Sinus lift tissue engineering using autologous pulp micro-grafts: A case report of bone density evaluation - Giorgio Brunelli; Alessandro Motroni; Antonio Graziano; Riccardo D'Aquino; Ilaria Zollino; Francesco Carinci (Wolters Kluwer Medknow Publications, 2013)
Background: Although autografts are the standard procedure for bone grafting, the use of bone regeneration by means of dental pulp stem cell is an alternative that opens a new era in this field. Rigenera Protocol is a new technique able to provide the surgeon autologous pulp micro-grafts. Materials and Methods: At the Department of Oral Surgery, Don Orione Hospital, Bergamo, Italy, one patient underwent sinus lift elevation with pulp stem micro-grafts gentle poured onto collagen sponge. A CT scan control was performed after 4 months and DICOM data were processed with medical imaging software which gives the possibility to use a virtual probe to extract the bone density. Pearson's Chi-square test was used to investigate difference in bone density (BD) between native and newly formed bone. Results: BD in newly formed bone is about the double of native bone. Conclusion: This report demonstrated that micro-grafts derived from dental pulp poured onto collagen sponge are a useful method for bone regeneration in atrophic maxilla.